Upconverting nanoparticles as primary thermometers and power sensors - Martins, Joana Costa; Skripka, Artiom; Brites, Carlos D. S.; Benayas, Antonio; Ferreira, Rute A. S.; Vetrone, Fiorenzo; Carlos, Luís D. (Frontiers in Photonics, 2022)
Luminescence thermometry is a spectroscopic technique for remote temperature detection based on the thermal dependence of the luminescence of phosphors, presenting numerous applications ranging from biosciences to engineering. In this work, we use the Er3+ emission of the NaGdF4/NaGdF4:Yb3+,Er3+/NaGdF4 upconverting nanoparticles upon 980 nm laser excitation to determine simultaneously the absolute temperature and the excitation power density. The Er3+ 2H11/2→4I15/2 and 4S3/2→4I15/2 emission bands, which are commonly used for thermometric purposes, overlap with the 2H9/2 →4I13/2 emission band, which can lead to erroneous temperature readout. Applying the concept of luminescent primary thermometry to resolve the overlapping Er3+ transitions, a dual nanosensor synchronously measuring the temperature and the delivered laser pump power is successfully realized holding promising applications in laser-supported thermal therapies.